Learning from the Pandemic: Structural Implications of Food Parcel Distribution Scheme in South Africa - Oratilwe Mokoena; Tshepo Ramarumo; , Solly Matshonisa Seeletse; Sam Thembelihle Ntuli (Community Development Journal, 2023)
The lack of inclusive governance and collaboration among various stakeholders and institutions to develop long-term strategies to alleviate food insecurity is an emerging pandemic during times of distress. The objective of the study is to develop an anti-corruption mechanism (food distribution aptitude for eligibility) that can remedy the structural implications of food parcel corruption during a pandemic. A qualitative exploratory review approach was adopted in the study. The reviewed studies revealed that the currently existing systems of food distribution failed due to poor recipient identification and vetting, systems manipulation by officials, lack of tracking devices during distribution, and ghost recipients. The study concludes that the divisions, bureaucracy, maladministration and corruption revealed in literature among the government have adversely impacted the welfare of the vulnerable and marginalized groups who reside in the informal settlements. Those in need of food parcels suffer at the hands of corrupt officials and their family members due to an unmonitored distribution scheme. The study model is expected to assist non-profit organizations, and government initiatives in selecting worthy beneficiaries during and post pandemics. The model is also expected to assist in removing the potential ills of the system, minimize system manipulation and corruption, and ensure transparency during food parcel distribution to the needy in times of distress.